IDENTIFIKASI JENIS PENYAKIT PADA TANAMAN JATI (Tectona grandis Linn.F) PADA HUTAN TANAMAN RAKYAT DUSUN TELAGA KODOK, PROVINSI MALUKU - Wa Nurjana Mustafa; Cornelia Wattimena; Fransina Latumahina (Jurnal Hutan Tropis, 2019)
Identification of Types of Diseases in Teak Plants (Tectona grandis Linn. F) in the Community Plantation Forest of Telaga Kodok Hamlet, Leihitu District, Central Maluku Regency, because it can be used as a guide for proper prevention and control.The purpose of this research is to know the types of diseases that attack the teak plants and to know the intensity of damage caused by the attack of the disease. This research was conducted at Dusun Telaga Kodok, Leihitu Sub-district of Central Maluku District from September to December 2017. Sampling was conducted on an area of 1 Ha, and each sample plot was observed throughout the plant. Observation of data taken include primary data and secondary data. The results of the study The disease found in the study site was leaf rust disease coused by Oliveae tectonae mushroom which showed 3 types of symptoms, namely the presence of small patches and large patches, brown leaf spot with curled leaf edges and brownish yellow patches which caused hollow leaves.. The intensity of the attack due to leaf rust disease has an average value of 36.43% included in the category of moderate damage.